The Community Empowerment Strategy in Protected Forest Management through Community-Based Ecotourism Development in Kalibiru Village, Kulon Progo Regency - Wiyono Wiyono; Rochmad Hidayat; Silvi Nur Oktalina (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2020)
The forest management strategies in Indonesia are starting to change from state-based forest management to community-based forest management. The changing of forest management strategies can be seen in the implementation of the Social Forestry Program at Kulon Progo Regency. This study aimed to know the strategies and benefits of community empowerment in managing protected forests by ecotourism. This research conducted on July – October 2019 in the forest farmer group of Mandiri at Kalibiru Village, Kulon Progo Regency. Data collection was done by several methods including (1) In-depth interview to the head of forest farmer group; (2) Focus group discussion with the committee of forest farmer group; (3) Field observation; and (4) Secondary data review. The data analyzed by descriptive method. The results of the study indicated that the forms of community empowerment strategies in protected forest management carried out by KTHKm Mandiri included: (1) Institutional management strategies through strong institutional governance of farmer groups; (2) Forest area management strategies through the application of the concepts of resources-based management, ecosystem-based management, and landscape-based management; (3) Forest business management strategy through the application of the concept of community-based ecotourism. The existence of Kalibiru Ecotourism has been proven to provide economic benefits to members of the group, as well as residents of the Kalibiru and surrounding communities, in the form of (1) profit sharing; (2) employment; (3) new business opportunities; and (4) social funding assistance. The existence of Kalibiru Ecotourism has also led to social changes in the residents of the Kalibiru and surrounding communities. These social changes included two dimensions, namely: (1) changes in orientation at the individual farmer level; (2) orientation changes at the farmer group level.